2018
DOI: 10.1111/cpf.12521
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal left ventricular function is globally depressed within a week of STEMI

Abstract: Sixty percent of stroke volume (SV) is generated by atrioventricular plane displacement (AVPD) in a healthy left ventricle (LV). The aims were to determine the effect of ST-elevation myocardial infarction (STEMI) on AVPD and contribution of AVPD to SV and to study the relationship between AVPD and infarct size (IS) and location. Patients from CHILL-MI and MITOCARE studies with cardiovascular magnetic resonance within a week of STEMI (n = 177, 59 AE 11 years) and healthy controls (n = 20, 62 AE 11 years) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
3
9
0
1
Order By: Relevance
“…Romano et al used death as a primary endpoint, which might serve as an explanation why their reported cut-off for lateral MAPSE (9 mm) is equal as we found for septal MAPSE. However, Pahlm et al reported a decrease in global and regional MAPSE in infarcted as well as remote myocardium, supporting our thesis that septal MAPSE provides prognostic information regardless of infarct localization [32]. Based on the significantly higher predictive value of septal MAPSE compared with lateral and average MAPSE in our population as well as on the independency of MAPSE decrease from infarct location, we consider the exclusive measurement of septal MAPSE to be reasonable.…”
Section: Discussionsupporting
confidence: 87%
“…Romano et al used death as a primary endpoint, which might serve as an explanation why their reported cut-off for lateral MAPSE (9 mm) is equal as we found for septal MAPSE. However, Pahlm et al reported a decrease in global and regional MAPSE in infarcted as well as remote myocardium, supporting our thesis that septal MAPSE provides prognostic information regardless of infarct localization [32]. Based on the significantly higher predictive value of septal MAPSE compared with lateral and average MAPSE in our population as well as on the independency of MAPSE decrease from infarct location, we consider the exclusive measurement of septal MAPSE to be reasonable.…”
Section: Discussionsupporting
confidence: 87%
“…The results in our study are in line with previous clinical studies reporting that AVPD decreases after myocardial infarction (1,6,25,37). This experimental study shows how the SV and related cardiac parameters change as a result of decreased AVPD after AMI, which is not possible to investigate in clinical studies, where a baseline examination is practically difficult.…”
Section: Sv Vs Avpdsupporting
confidence: 91%
“…All results combined suggest that AVPD is likely to be globally reduced after AMI. This has also recently been reported by Pahlm et al in patients (n ϭ 177) within a week after ST-elevation myocardial infarction (37).…”
Section: Avpd: Anteroseptal Vs Remote Myocardiumsupporting
confidence: 83%
See 1 more Smart Citation
“…Global longitudinal LV shortening measured as global longitudinal strain (GLS) can be used to detect MI [6], and has prognostic value superior to ejection fraction (EF) [7]. Longitudinal LV systolic shortening is also reflected by the atrioventricular plane displacement (AVPD) [8] which has been shown to be the main contributor to LV stroke volume in healthy individuals [9] and in patients with STEMI, both in the sub-acute [10] and the chronic phases [11]. GLS and AVPD differs as GLS quantifies myocardial shortening in the long-axis direction and the latter measure the summed effect of this contraction on the AV-plane.…”
Section: Introductionmentioning
confidence: 99%